STUDENTS PERSPECTIVE TOWARD THE USE OF PADLET TO WRITE A RECOUNT TEXT TO IMPROVE STUDENTS’ WRITING ABILITY - Ramadhani, Farah Anisa; Wardani, Pramudita Kumuda; Zakia, Ryan Ahmad Ghulaman (Transpublika Publisher, 2024)
This study aims to report the results of students’ perspective using the Padlet website to improve students’ writing ability in writing recount text. This study was conducted at SMPN 5 Malang. The subject was 31 students from 6F4 class, the eighth graders of SMPN 5 Malang. This study utilized a qualitative descriptive design. To collect the data, the researchers used a set of questionnaires. The questionnaires contain 10 statements and are distributed to students. The data were analyzed, put into tables and summarized in percentages and description form. The results of the analysis show that the students show a positive perspective regarding the use of Padlet application in their writing ability in writing recount text.